MANAJEMEN KOLABORATIF DALAM PENGABDIAN MASYARAKAT DENGAN PEMANFAATAN PAKAIAN LAYAK PAKAI SEBUAH BEST PRACTICE DI KOTA BENGKULU - Jasita Apriyani; Randy Oktapiansyah; Rahma Ardita; Ashadi Cahyadi (Al-Idaroh: Media Pemikiran Manajemen Dakwah, 2023)
This research aims to analyze, explain or retell the existence of collaborative management in community service activities by using appropriate clothing as a best practice in the city of Bengkulu which is carried out by students of missionary management and religious institutions in the city of Bengkulu, namely the Daarul Armina Foundation. This research was carried out using a qualitative descriptive method, explaining the existence of collaborative management in supporting the success of activities. The results of this research are collaborative management is carried out by several stakeholders, namely the university (propagation management students), the Daarul Armina Foundation, TPA, the market and the community as consumers. This collaboration can provide many benefits for the stakeholders involved, this activity can also be used as a recommendation as an activity for student and community movements.for computerization. Research and abstract title search made easy with these keywords